A New Lane Detection Method Based on Vanishing Point Estimation with Probabilistic Voting - Yoo, Ju Han; Park, Sung-Kee; Kim, Dong Hwan (2015 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2015)
In this paper, we present a new lane detection method based on vanishing point estimation. We first estimate the vanishing point with probabilistic voting using the line segment strength, then detect lanes by applying the flooding watershed algorithm.